The Whistle of My Father - Herrero, Herbert (Likhaan: The Journal of Contemporary Philippine Literature, 2023)
“The Whistle of My Father” is about a man who chose a life away from family in his desire to provide for the future he thought his children deserved—a path taken by many Filipino fathers in the 1980s and in the decades that followed. This is a story told through the eyes of a son, surely to resonate with other sons whose fathers have realized their dreams for them by working in a foreign land.